Immune Checkpoint Inhibitors New Insights and Recent Progress - Raza, Afsheen (IntechOpen, 2023)
Immune Checkpoint Inhibitors - New Insights and Recent Progress explores a vast array of subjects related to immune checkpoint inhibitors and presents novel insights in this emerging field. Chapters address such topics as mechanistic approaches of emerging immune checkpoint inhibitors, their role in clinical and pre-clinical trials, the manipulation of the system by immune-related adverse events that hinder the utility of these immune molecules, and the predictive and prognostic aspects of these molecules as biomarkers of response in immunotherapy. The book is useful for students, clinicians, and scientists to gain updated information on managing patients treated with immune checkpoint inhibitors.